Editorial: understanding differences in patient response to ondansetron in irritable bowel syndrome with diarrhoea—are we any closer? Authors' reply. Issue 7 (18th September 2019) - Gunn, David; Garsed, Klara; Lam, Ching; Singh, Gulzar; Lingaya, Melanie; Wahl, Verena; Niesler, Beate; Henry, Amanda; Hall, Ian; Whorwell, Peter; Spiller, Robin
Abstract : LINKED CONTENT This article is linked to Gunn et al and Black et al papers. To view these articles, visithttps://doi.org/10.1111/apt.15420 andhttps://doi.org/10.1111/apt.15455 .